Suboptimal bonding impairs hormonal, epigenetic and neuronal development in preterm infants, but these impairments can be reversed. (8th December 2015) - Kommers, D; Oei, G; Chen, W; Feijs, L; Bambang Oetomo, S
Abstract: This review aimed to raise awareness of the consequences of suboptimal bonding caused by prematurity. In addition to hypoxia–ischaemia, infection and malnutrition, suboptimal bonding is one of the many unnatural stimuli that preterm infants are exposed to, compromising their physiological development. However, the physiological consequences of suboptimal bonding are less frequently addressed in the literature than those of other threatening unnatural stimuli. Conclusion: This review found that suboptimal bonding significantly impaired hormonal, epigenetic and neuronal development, but these impairments could be reversed by bonding interventions. This suggests that neonatal intensive care units should focus more on interventions that optimise bonding. Abstract :